Genetic variability among cassava accessions based on SSR markers - Ribeiro,Márcia de Nazaré Oliveira (2011)
The aim of this study was to characterize and estimate the genetic similarity among 93 cassava accessions. The DNA amplification was performed with 14 microsatellite primers. The amplification products were separated by a polyacrylamide gel electrophoresis, showing a polymorphism formation, through which the accessions were discriminated against. The genetic similarity among accessions of cassava was estimated by the Dice coefficient. Cluster analysis was carried out using the UPGMA method. The polymorphic primers amplified a total of 26 alleles with 2-4 alleles per loci. The genetic similarity ranged from 0.16 to 0.96. The average values for observed and expected heterozygosity were 0.18 and 0.46, respectively. Twenty genetic similarity clusters were determined, demonstrating diversity among accessions, suggesting the possibility of heterotic hybrid generation.